Serum C-reactive protein metabolite (CRPM) is associated with incidence of contralateral knee osteoarthritis - Anne-Christine Bay-Jensen (Nature Portfolio, 2021)
Abstract The heterogeneous nature of osteoarthritis (OA) and the need to subtype patients is widely accepted in the field. The biomarker CRPM, a metabolite of C-reactive protein (CRP), is released to the circulation during inflammation. Blood CRPM levels have shown to be associated with disease activity and response to treatment in rheumatoid arthritis (RA). We investigated the level of blood CRPM in OA compared to RA using data from two phase III knee OA and two RA studies (N = 1591). Moreover, the association between CRPM levels and radiographic progression was investigated. The mean CRPM levels were significantly lower in OA (8.5 [95% CI 8.3–8.8] ng/mL, n = 781) compared to the RA patients (12.8 [9.5–16.0] ng/mL, n = 60); however, a significant subset of OA patients (31%) had CRPM levels (≥ 9 ng/mL) comparable to RA. Furthermore, OA patients (n = 152) with CRPM levels ≥ 9 ng/mL were more likely to develop contra-lateral knee OA assessed by X-ray over a two-year follow-up period with an odds ratio of 2.2 [1.0–4.7]. These data suggest that CRPM is a blood-based biochemical marker for early identification OA patients with an inflammatory phenotype.